Economic Aspects of Russian-Baltic Relations in 2007—2008 - Mezhevich Nikolay (Baltic Region, 2009)
The influence of the events related to the transfer of the remains and the monument to Soviet soldiers in central Tallinn on the Russian cargo transit flows through the Baltic Sea region is described. The author shows that there has been a redistribution of Russian cargoes and their shipment through the ports of Latvia and Lithuania lately. According to the author, the positive dynamics of Russian-Latvian and Russian-Lithuanian relations should be sustained, proceeding from the assumption that sooner or later, the logic of economic cooperation may prove stronger than political considerations.